2021
DOI: 10.33533/jpm.v15i1.2491
|View full text |Cite
|
Sign up to set email alerts
|

Decreas of BCL-2 Expression by Ethanol Extract of Ocinum basilicum L. Leaves in Breast Cancer Cells

Abstract: Ocimum basilicum L has proven to have in vitro cytotoxic activity against breast cancer cells. Pathways that cause cell death can involve one of the proteins, which is BCL-2. This study aims to determine the decrease of BCL-2 protein expressions in breast cancer cells (T47D and MCF-7) tat are treated with the ethanol extract of Ocimum basilicum L. Ocimum basilicum L. was extracted using the maceration method with 70% ethanol solvent. The concentration of ethanol extract of Ocimum basilicum L. used to see the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…Corroborating this study, it was previously demonstrated that the ethanolic extract of O. basilicum decreases the expression of the Bcl-2 protein in breast cancer cells (T47D and MCF-7) in vitro at concentrations of 199 and 388 µg/ mL, respectively 39 . Moreover, O. basilicum extract reverts the increase of Bcl-2 content from testicular tissue induced by acute exposure of cadmium in albino rats, suggesting that the effect of Basil extract on Bcl-2 is maintained in tissues other than breast tissue.…”
Section: Resultssupporting
confidence: 68%
“…Corroborating this study, it was previously demonstrated that the ethanolic extract of O. basilicum decreases the expression of the Bcl-2 protein in breast cancer cells (T47D and MCF-7) in vitro at concentrations of 199 and 388 µg/ mL, respectively 39 . Moreover, O. basilicum extract reverts the increase of Bcl-2 content from testicular tissue induced by acute exposure of cadmium in albino rats, suggesting that the effect of Basil extract on Bcl-2 is maintained in tissues other than breast tissue.…”
Section: Resultssupporting
confidence: 68%